Membangun Karakter Anak Melalui Pendidikan Karakter - Maharani, Laila (Universitas Islam Negeri Raden Intan Lampung, 2014)
Various forms of crime and immoral acts in the handling of children and adolescents show that our students have not a good character. This indicates the need for character education that is appropriate for the child, which is not just knowledge and doctrine but rather reaches the emotional area. In the process of forming qualified human beings, character education is necessary for people not only to know virtue (knowing the good) but also feel (feeling the good), love (loving the good), want (desiring the good) and doing good (acting the good).